(untitled) (Ciudades, 2017)
The General Telecomunications Law, April 24, 11/1998, attempts to regulate the current and future telecommunications deployments that fulfill the autonomy and local administrations laws. The changes in Cell telephony´s from GSM to UMTS and beyond, force to also do changes in the antennas and poles. People dislike these types of changes. Base Stations in cities can be subjected to a general plan of deployment, laws concerning the ambiental impact and construction, aperture and put in operation. Landlines haven´t raised public awareness until recently. Pole number was low and deployment focus on telephony´s companies´ buildings or in strategic taller buildings and towers placed far from populated areas. New companies that demand new installations face the dilemma of technical conflicts because they must share the space under the sidewalks in downtown plus the inconvenience for the construction (blocked streets, need to get licenses etc). We can say that companies are making new compromises between better deployments and public awareness.